Etnomatematika: Eksplorasi Budaya Sasak â€œNyongkolanâ€ Sebagai Sumber Belajar Matematika - Masjudin, Masjudin; Suastra, I Wayan; Arnyana, Ida Bagus Putu; Fatwini, Fatwini (Media Pendidikan Matematika, 2024)
Mathematics is often perceived as an abstract discipline far removed from everyday life, yet its concepts can be found in various cultural traditions. This study aims to explore the Sasak community’s Nyongkolan tradition in Lombok as a source of mathematics learning through an ethnomathematical approach. The research employed a descriptive qualitative method with a field research approach. Data were collected through direct observation, interviews with cultural figures and experts, and documentation of Nyongkolan elements. The analysis involved data reduction, presentation, and drawing conclusions to identify the relationship between Nyongkolan cultural elements and mathematical concepts.The results revealed that the Nyongkolan tradition is rich in mathematical elements that can be utilized in education. Geometric patterns on songket fabric can be used to teach plane geometry and geometric transformations. The formation of participant rows reflects concepts of sequences, series, and numerical patterns. Musical instruments such as gendang beleq and gongs, shaped like cylinders and circles, serve as tangible examples for understanding spatial geometry. Additionally, estimating the distance and time of the Nyongkolan procession can be applied in teaching algebra and measurement. This tradition also embodies cultural values that strengthen community bonds, respect, and social identity. In conclusion, integrating the Nyongkolan tradition into mathematics learning not only enhances students’ conceptual understanding but also preserves local traditions. The findings of this study are expected to serve as a reference for educators in developing culturally-based learning materials, thereby creating contextual and meaningful learning experiences